Astigmatismo inducido postoperatorio de catarata senil en paciente de 65 años de edad. - Saltos Yaguana, Cecilia María (2020)
The present clinical case is about a patient from Santo Domingo de los Tsáchilas who came for a visual consultation due to a deficit in her visual acuity. The patient is sixty-five years old and was operated on for senile cataract at the Eloy Alfaro de la Ophthalmological Hospital. Ciudad Latacunga, the importance of this clinical case is because after a short time I reported postoperative induced astigmatism, cataract being a pathology that produces decreased visual acuity in its early stages and if it is allowed to advance it produces total blindness due to hyper maturation of the lens. It constitutes a very dangerous factor since by letting time pass a functional problem can be established in childhood such as amblyopia, for the extraction of the lens there are various techniques of how is phacoemulsification with implantation of an intraocular lens and the most current in technology the Femtosecond. The objective of this clinical case is to identify the cause of postoperative induced astigmatism of senile cataract. For this, a series of objective, subjective and complementary examinations were carried out. Retrospective, descriptive, observational, and bibliographic methods of the patient were used, finding as a result that he suffered from blurred vision, headache, tearing, and redness of the eyes due to an allergy caused by contact with irritants typical of work, after a meticulous study of the ophthalmological and optometric tests and diagnosis, it is concluded that postoperative induced Astigmatism of senile cataract is due to enlargement of the tunnel incision to implant the intraocular lens.